2019
DOI: 10.21873/anticanres.13577
|View full text |Cite
|
Sign up to set email alerts
|

Wedelolactone Targets EZH2-mediated Histone H3K27 Methylation in Mantle Cell Lymphoma

Abstract: Background/Aim: Enhancer of zeste homolog 2 (EZH2), the catalytic subunit of polycomb repressive complex 2 (PRC2), possesses histone N-methyltransferase (HMT) activity and plays an essential role in cancer initiation and development. The aim of the present study was to investigate the potential of Wedelolactone (WL) to inhibit the methylation activity of EZH2. Materials and Methods: The mantle cell lymphoma (MCL) cell line, Mino, was treated with WL, while untreated cells were used as control. HMT activity and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“… 29 WEL targeted EZH2-mediated histone H3K27 methylation in mantle cell lymphoma. 26 In the present study, loss of PTPN2 aggravated HK-2 cell damage via elevating the production of inflammatory cytokines and promoting apoptosis in the presence of LPS and WEL. Hence, elevating the levels of PTPN2 may be an effective therapeutic method for the treatment of LPS-induced renal injury.…”
Section: Discussionsupporting
confidence: 47%
“… 29 WEL targeted EZH2-mediated histone H3K27 methylation in mantle cell lymphoma. 26 In the present study, loss of PTPN2 aggravated HK-2 cell damage via elevating the production of inflammatory cytokines and promoting apoptosis in the presence of LPS and WEL. Hence, elevating the levels of PTPN2 may be an effective therapeutic method for the treatment of LPS-induced renal injury.…”
Section: Discussionsupporting
confidence: 47%
“…EZH2 is expression is low in the normal liver, and is associated with methylation of histone H3K27 and recruitment of methyltransferases, which are involved in DNA replication for cancer progression, and stem cell maintenance and differentiation of other cell lineages, such as immune cells (32,33). Several studies have confirmed its prognostic value and importance in various types of cancer, including lymphoma, glioma, head and neck carcinoma, and cervical neoplasia (34)(35)(36)(37)(38). Novel therapeutic methods have been developed to target EZH2, although high expression of EZH2 is not always correlated with the malignancy of a cancer, such as in colorectal cancer (39)(40)(41).…”
Section: Discussionmentioning
confidence: 99%
“…In an effort to understand the mechanism of action, we found that inhibition of EZH2 by chidemide or shEZH2 decreased expression of H3K27me3 and DNMT3A, and increased cytotoxic sensitivity in AML cells and stem/progenitor cells. EZH2 is a histone methyltransferase associated with transcriptional repression through dimethylation and trimethylation of H3K27 (H3K27me2/3), and EZH2 mediated H3K27 methylation contributes to pathological process and poor prognosis in hematological malignancies [57,58]. Depletion of EZH2 suppresses the expression of H3K27me3, and inhibits survival of LSC in mixed lineage leukemia [59].…”
Section: Discussionmentioning
confidence: 99%